Bull's island eaudiobook - Frank, Dorothea Benton (Lowcountry Tales, 2008)
Dorothea Benton Frank is a New York Times best-selling author whose books are prized by fans who enjoy her heartfelt stories. In Bull's Island, she offers a fun and original twist on Shakespeare's classic, Romeo Juliet. The blue-blooded Langley family and the new-money Barretts are at odds over the impending wedding of JD and Betts. And then a shocking event on the night of their engagement changes everything.